Determination of the thermodynamic properties of poly [2-(3-phenyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate-co-methacrylic acid] at infinite dilution by inverse gas chromatography - Kaya, I; Demirelli, K (Scientific Technical Research Council Turkey, 2001)
Some thermodynamic quantities were obtained for the interactions of poly [2-(3-phenyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate-co-methacrylic acid] Poly (PCHEMA-co-MA) with alcohols, ketones, acetates, aromatics and n-alkanes by inverse gas chromatography in the temperature range of 150-180 degreesC. The specific retention volumes, Vg degrees. weight fraction activity coefficients of solute probes at infinite dilution, Omega (infinity)(1) and Flory-Huggins thermodynamic interaction parameters, chi (infinity)(12) between polymers and solvents were determined. The partial molar free energy, DeltaG(1)(infinity), the partial molar heat of mixing, DeltaH(1)(infinity). at infinite dilution and the solubility parameters of the polymer, delta (2), were calculated. The copolymer was characterized by H-1-NMR, FT-IR and DSC analyses.
Keywords: poly [2-(3-phenyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate-co-methacrylic acid]; inverse gas chromatography; polymer-solvent interactions